2017
DOI: 10.1103/physrevlett.118.155001
|View full text |Cite
|
Sign up to set email alerts
|

Self-Generated Magnetic Fields in the Stagnation Phase of Indirect-Drive Implosions on the National Ignition Facility

Abstract: Three-dimensional extended-magnetohydrodynamic simulations of the stagnation phase of inertial confinement fusion implosion experiments at the National Ignition Facility are presented, showing selfgenerated magnetic fields over 10 4 T. Angular high mode-number perturbations develop large magnetic fields, but are localized to the cold, dense hot-spot surface, which is hard to magnetize. When low-mode perturbations are also present, the magnetic fields are injected into the hot core, reaching significant magneti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
80
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 79 publications
(81 citation statements)
references
References 24 publications
1
80
0
Order By: Relevance
“…Capsule-only simulations are performed using the 3-D radiation extended-magnetohydrodynamics code Gorgon, 11,17 which uses the same framework as in the Chimera code. 14 The radiation transport is non-diffusive, using P 1/3 automatic flux limiting.…”
Section: Simulation Setupmentioning
confidence: 99%
See 1 more Smart Citation
“…Capsule-only simulations are performed using the 3-D radiation extended-magnetohydrodynamics code Gorgon, 11,17 which uses the same framework as in the Chimera code. 14 The radiation transport is non-diffusive, using P 1/3 automatic flux limiting.…”
Section: Simulation Setupmentioning
confidence: 99%
“…This is in contrast to hot-spots without an applied external magnetic field, where the magnetic flux is expected to be self-generated by the Biermann Battery mechanism; Righi-Leduc can be an important heat-loss process in these moderately magnetised (x e s e % 1) hot-spots. 11 The Lorentz force from a magnetic field onto a plasma is given by…”
Section: Introductionmentioning
confidence: 99%
“…Note that, although the total current in the plasma is zero, the current arising from fast ion-electron collisions, j 0 eα , can contribute to heat flow. To investigate (32) we choose a mono-energetic population of α particles with E α = 3.45 MeV in a DT plasma. In fig.…”
Section: A Heat Flow In An Unmagnetized Plasmamentioning
confidence: 99%
“…This could be of interest in a number of scenarios in which large magnetic fields are present in burning inertial fusion plasmas. These include self-generated magnetic fields 32 and schemes in which a large magnetic field is imposed on the plasma in order to suppress electron thermal conduction and reduce heat losses from the hot fuel. Examples of such schemes that are currently being investigated include indirect-drive ICF with an imposed magnetic field 33,34 and magneto-inertial fusion schemes such as MagLIF.…”
Section: B Heat Flow In a Magnetized Plasmamentioning
confidence: 99%
“…Under such conditions the electron distribution function deviates from its equilibrium Maxwellian form and the classical (Braginskii) heat transport model [9] breaks down [10].Experimental measurements have demonstrated that non-local heat transport effects are important in nanosecond time scale laser-solid interactions [11,12], and must be taken into account to align ICF simulations with experimental predictions [13][14][15]. It has been shown that there can be a significant interplay between the non-local heat flux effects and the magnetic field dynamics [16,17].Self-generated magnetic fields have been measured in ablation phase ICF experiments [18,19] and are predicted to be important in a variety of ICF relevant conditions [16,20]. Crossed number density, n e , and temperature, T e , gradients, that occur at perturbations in the laser energy deposition, generate magnetic fields through the Biermann battery mechanism, ∂ t B = −∇n e × ∇T e /(|e|n e ) [21,22].…”
mentioning
confidence: 99%